The Significance of Colors in the Divan (Stirring Argument) by the poet (Hazervan Abdullah) - Taher, Nizar; Ismail, Rondik (Humanities Journal of University of Zakho, 2021)
This study is an attempt to show how to embody the significance of colors in the poetic text, through which we can understand the meaning of the text in a more clear way, and we also know the artistic method of formulating poems more clearly. This study entitled (The Significance of Colors in the Divan (Stirring Argument) by the poet (Hazervan Abdullah) was divided into two parts. We devoted the first section to the theoretical aspect of the study and presented in it a theoretical background on the term, concept and what color. Poetic texts for the purpose of finding the hidden connotation of color in the poems. It turns out that eight colors (black, white, red, green, yellow, burgundy, maronite, purple) have been embodied in the poems, as well as showing us that the poet was able to express through the connotation of colors On the topics of his poems such as (sadness, pain, hope, worries, and pent-up desires).